La ancianidad en el Derecho Constitucional argentino - Novelli, Mariano Horacio (2018)
Historically, the problem of old age has not been an object of interest to the legal debate. Only in recent years, this complex stage of life has begun to be addressed, especially by Civil Law, Criminal Law and Philosophy of Law. However, there are still few studies which focus on the constitutional perspective and the rights of the elderly. That is the profile of the present work, which carries out a detailed and comparative analysis of the regulations of the highest hierarchy in Argentina. It emphasizes that, in accordance with postmodern times, the elderly person is a weak individual who frequently becomes a victim of economic, structural, physical, psychological and sexual violence. It also stresses that Law is an instrument of great value to overcome this weakness, by strengthening the living conditions and status of the elderly.